The effect of flipped learning on EFL learners’ public speaking in Taiwan - Rachid Bezzazi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
This study investigates the effectiveness of flipped learning on English as a Foreign Language (EFL) learners’ public speaking. An experimental design was implemented throughout the study, for which the researcher used convenience sampling. Seventy-nine sophomore students, from two intact English Public Speaking classes, were divided into a flipped learning group (FLG) and a conventional instruction group (CIG). This happened over a 12-week period where the focus was to investigate how a language learner’s experience of flipped learning or conventional instruction affected their English public speaking. The author used quantitative and qualitative methods to collect data: a pre- and post-in-class speech and a 250-word post-treatment reflective essay. Both an independent and paired t-test were used to analyze the scores of the speeches, whereas coding was used to specify the themes that emerged from the qualitative data. The results revealed that the FLG significantly outperformed the CIG in the areas of body language and paralanguage. In addition, they did better in the areas of content and organization, and developed other skills as will be detailed later. The findings can be an impetus for EFL instructors to adopt flipped learning in an English public speaking course.